If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 25z + -4 = 96 Reorder the terms: -4 + 25z = 96 Solving -4 + 25z = 96 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 25z = 96 + 4 Combine like terms: -4 + 4 = 0 0 + 25z = 96 + 4 25z = 96 + 4 Combine like terms: 96 + 4 = 100 25z = 100 Divide each side by '25'. z = 4 Simplifying z = 4
| r/24=-3 | | x-.2x=656 | | 7y^2-23y-6=0 | | 59=25x | | 2-x=3018 | | 1.6a+(4)=0.032 | | 282.36=6.42(40)+1.5(6.42)v | | 2(2x-1)=6 | | 14-6=n | | 5+78=52x+21 | | solvep=2g+20forg | | -3x+1-(-4x-6)=10 | | 6(2x+1)=25 | | 19-5/2x=4 | | 9(x+3)+9=9x+3 | | f(3)=2(3)+1 | | 6.3+0.5x=8 | | (3x+1)(5x-3)= | | 5(3x+8)=20 | | 2x+9=14-7x | | ax=b+2x | | 3+5x=3+x | | 0=-x^2+2x-8 | | -9=3/8n | | x^2+y^3-x^2y^2=64 | | 2(x+2)-9=3x-17 | | 7x-27/5x= | | 769=(x*40)+(1.5x*15) | | 6(x+3)-(4n+9)= | | 4(-6)+8y=0 | | 10x-20=5x+8 | | 0.70x+0.10(480-x)=0.60 |